Optical properties of nano-structured Pt/FTO counter electrode for QDSSCs - Yahia, I.S.; Zahran, H.Y.; Fatehmulla, Amanullah; Farooq, W.A.; Aslam, M.; Ali, S. Mansoor; Yakuphanoğlu, Fahrettin (My University, 2013)
Nano-structured platinum (Pt) thin film on fluorine doped tin oxide (FTO) coated on glass substrate was prepared via sputtering technique for quantum dot-sensitized solar cells (QDSSCs). Pt/FTO counter electrode surface morphology was studied using AFM images which revealed the nanorods collection on cylindrical tubes with film roughness 18.63 nm. Transmittance and reflectance measurements of FTO substrate as well as Pt/FTO were carried out in the wavelength range 200-2500 nm. Optical constants (n and k) were calculated at different wavelengths by applying Kramers-Kronig Transformations. The results obtained have been compared and discussed in terms of optimum conditions for a counter electrode. Our efforts are to establish a QDSSC based on nano Pt/FTO counter electrodes. Our work targets can enhance in the near future for photo-counter electrodes applied in QDSSCs. © 2013 IEEE.
2013 Saudi International Electronics, Communications and Photonics Conference, SIECPC 2013 -- 27 April 2013 through 30 April 2013 -- Riyadh -- 98388
Keywords: Kramers-Kronig Transformations; Nanostructure; Optical constants; Pt/FTO counter electrode; QDSSC